Ceramide Synthase 6 Is a Novel Target of Methotrexate Mediating Its Antiproliferative Effect in a p53-Dependent Manner - Fekry, Baharan (PLoS One, 2016)
We previously reported that ceramide synthase 6 (CerS6) is elevated in response to folate stress in cancer cells, leading to enhanced production of C(16)-ceramide and apoptosis. Antifolate methotrexate (MTX), a drug commonly used in chemotherapy of several types of cancer, is a strong inhibitor of folate metabolism. Here we investigated whether this drug targets CerS6. We observed that CerS6 protein was markedly elevated in several cancer cell lines treated with MTX. In agreement with the enzyme elevation, its product C(16)-ceramide was also strongly elevated, so as several other ceramide species. The increase in C(16)-ceramide, however, was eliminated in MTX-treated cells lacking CerS6 through siRNA silencing, while the increase in other ceramides sustained. Furthermore, the siRNA silencing of CerS6 robustly protected A549 lung adenocarcinoma cells from MTX toxicity, while the silencing of another ceramide synthase, CerS4, which was also responsive to folate stress in our previous study, did not interfere with the MTX effect. The rescue effect of CerS6 silencing upon MTX treatment was further confirmed in HCT116 and HepG2 cell lines. Interestingly, CerS6 itself, but not CerS4, induced strong antiproliferative effect in several cancer cell lines if elevated by transient transfection. The effect of MTX on CerS6 elevation was likely p53 dependent, which is in agreement with the hypothesis that the protein is a transcriptional target of p53. In line with this notion, lometrexol, the antifolate inducing cytotoxicity through the p53-independent mechanism, did not affect CerS6 levels. We have also found that MTX induces the formation of ER aggregates, enriched with CerS6 protein. We further demonstrated that such aggregation requires CerS6 and suggests that it is an indication of ER stress. Overall, our study identified CerS6 and ceramide pathways as a novel MTX target.